Unique Alzheimer's Disease Challenge Reports in Malaysia - Atif Amin, Baig; Ahmad Zubaidi, A.latif; Nordin, Simbak; Wee, Kok Wei (2018)
Alzheimer’s disease (AD) is a chronic neurodegenerative disorder that usually starts slowly and worsens with time. It is a type of dementia, which presents with memory loss, thinking and behaviour problems.Itrose as serious health risk for the community and health sector. It affects individually, family, and health care in terms of quality of life. Patients mostly presents with early onset of memory impairment and additionally with sematic memory, executive functioning, visuospatial abilities and functional impairments. People with Alzheimer’s and dementia have some of the highest health care costs of any chronic condition. They are less likely than other older adults to live in the community, even though doing so results in lower health care costs than when individuals with Alzheimer’s or dementia live in a skilled nursing facility. In general we can divide the care of dementia patient into three types: independent living at home; home care with support and institutional care.